2010
DOI: 10.1111/j.1467-971x.2010.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid compounding in New Zealand English

Abstract: This study investigates hybrid compound formation of Maori and English terms in present day New Zealand English (NZE). On the background of Maori and English language contact, the phenomenon of hybrid compounding emerges as a process that, on the one hand, symbolizes the vitality of the Maori element in NZE and, on the other hand, marks the integration of Maori concepts in New Zealand culture. The investigation is based on a quantitative and qualitative analysis of the most frequent Maori loans in hybrid compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The pervasiveness of the loans was noted in both spoken and written New Zealand English (Kennedy and Yamazaki 1999), in newspaper media (Macalister 2006a;2006b;Davies and Maclagen 2006;Degani and Onysko 2010;Degani 2010), in children's books (Daly 2007), and in the work of many prominent New Zealand novelists (Keri Hulme, Witi Ihimaera, Alan Duff, Patricia Grace). Investigating the productivity of loans, Degani and Onysko (2010) found that many well-established loans do indeed "enter into productive processes of word formation" (2010: 231).…”
Section: Linguistic Context Of New Zealandmentioning
confidence: 99%
See 1 more Smart Citation
“…The pervasiveness of the loans was noted in both spoken and written New Zealand English (Kennedy and Yamazaki 1999), in newspaper media (Macalister 2006a;2006b;Davies and Maclagen 2006;Degani and Onysko 2010;Degani 2010), in children's books (Daly 2007), and in the work of many prominent New Zealand novelists (Keri Hulme, Witi Ihimaera, Alan Duff, Patricia Grace). Investigating the productivity of loans, Degani and Onysko (2010) found that many well-established loans do indeed "enter into productive processes of word formation" (2010: 231).…”
Section: Linguistic Context Of New Zealandmentioning
confidence: 99%
“…Investigating the productivity of loans, Degani and Onysko (2010) found that many well-established loans do indeed "enter into productive processes of word formation" (2010: 231). The use of Māori loans in TV media was studied by De Bres (2006) and unlike other language mediums, de Bres found that Māori loans were used only to a "limited extent in the mainstream television news" and "in highly restricted areas", "almost solely in Māori-related news items " (2006: 32).…”
Section: Linguistic Context Of New Zealandmentioning
confidence: 99%
“…The study takes a corpus‐based rather than corpus‐driven approach (Biber 2009) where words, formulaic expressions or multiword units (MWUs) were pre‐selected, and then analysed in the corpus to see how they were used. In order to expand the scope of the investigation, definitions and examples of MWUs and individual words were taken from a variety of writers on NZE, both academic (Bennett 1943; Deverson 1984; 1991; 1999; 2010; Bauer 1994; 2002; Macalister 2004; 2005; 2006; 2007a; 2007b; Orsman 1997; 1999; Bardsley 2005; 2009; Gordon and Deverson 1998; Degani and Onysko 2010; Gordon 2010b), and popular writing (McGill 1988; Cryer 2001; 2002; 2006; Wolfe and Barnett 2007; Brown 2008; Kirk 2008; Gordon 2010a). Additional supporting evidence comes from the New Zealand Dictionary Centre (NZDC) at Victoria University of Wellington, and from media use (Macalister 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the lexis of NZE, Bennett (1943: 81) noted almost 70 years ago that “the language of the New Zealanders has its own distinctive characteristics, its own blend of idioms and usages”. This paper investigates some of this language, expanding on a recent article (Degani and Onysko 2010) by examining not just “hybrid compounds of Maori and English terms” but both single words and formulaic multiword units (MWUs) in academic and popular writing. These, it is argued, are part of New Zealand's cultural scripts, “that is, its own set of assumptions and evaluations which are widely known and shared” (Wierzbicka 2001: 207).…”
Section: Introductionmentioning
confidence: 99%
“…Bell and Holmes ; Bauer and Holmes ; Holmes ) and the influence of Maori on New Zealand English (e.g. Matthews ; Hughes ; Macalister ; Degani and Onysko ). With a relatively strong focus on grammatical, lexical, syntactic and phonological features of New Zealand English we have gained a good understanding of a wide range of features associated with this particular variety of English.…”
Section: Introductionmentioning
confidence: 99%